ByzRev 04.2022.017: Ellen S. Schwartz (ed.), The Oxford Handbook of Byzantine Art and Architecture.: New York: Oxford University Press 2021. - Parpulov, Georgi (The Byzantine Review, 2022)
Ellen S. Schwartz (ed.), The Oxford Handbook of Byzantine Art and Architecture. New York: Oxford University Press 2021. XXX, 628 pp., 140 black-and-white illustr., 24 colour plates. – ISBN 978-0-19-027735-2 (₤ 97.00)